Assessing and Mitigating the Carbon Footprint of Products: A Comprehensive Analysis - Kivikali B. Chishi (International Journal of Environmental Planning and Development Architecture, 2024)
The environmental impact of human activities, particularly in the production and consumption of goods, has gained significant attention in recent years. The carbon footprint that products have is one important part of this impact. This research paper investigates and analyzes the carbon footprint of products, exploring the methods of assessment, key contributing factors, and potential mitigation strategies. By understanding the carbon footprint of products, consumers, producers, and policymakers can make informed decisions to promote sustainable practices and contribute to the collective effort to mitigate climate change. This comprehensive analysis provides valuable insights into the complex relationship between products and their environmental impact, offering a foundation for informed decision-making and sustainable action.
Keywords: Buildings; Carbon emissions; Climate change; Global Warming; Sustainability